Book Launch - Urban Violence. Security, Imaginary, Atmosphere - Pavoni, A.; Tulumello, S. (Book Launch - Urban Violence. Security, Imaginary, Atmosphere, 2023)
Book launch organised by Alberto Vanolo, University of Turin, with Giovanni Semi (Polito) and Carlo Genova (Unito) as discussant